Living with a new normal: women’s experiences following treatment for early-stage breast cancer or DCIS - Trusson, Diane (2013)
This thesis explores the experiences of 24 women who were treated for early-stage breast cancer (ESBC) or ductal carcinoma in situ (DCIS) in the UK between 6 months - 29 years previously. These experiences are important because better detection and treatments have resulted in increasing numbers of women surviving for longer. My own experience of ESBC, revealed in extracts from my research journal, brought both benefits and drawbacks to the research but ultimately resulted in a unique perspective. Participants accessed through a press release were interviewed in-depth. Data were then analysed using narrative and thematic analysis. Bury’s (1982) concept of illness as a biographical disruption was used as the theoretical framework but a consideration of the context revealed that ESBC/DCIS is not always experienced as disruptive. Analysis also revealed that the post-treatment period can present further challenges as loss of medical support can coincide with withdrawal of social support. Some participants reported feeling isolated and vulnerable post-treatment. Often their feelings were at odds with public expectations based on media representations of ‘successful’ breast cancer survivors, and the high profile of breast cancer charities which can suggest ‘pink fluffy’ imagery. Ongoing disruption to their bodies and relationships can mean that women feel in an ambiguous state which can be likened to a state of liminality (Turner, 1969). The current research combines the concepts of biographical disruption and liminality for the first time in a study of ESBC/DCIS, therefore enabling consideration of gendered aspects of the experience. In particular, the importance of breasts to femininity and sexuality can have implications for identity and relationships. I argue that, whilst women do not return to the ‘normality’ of pre-diagnosis, the wide range of experiences and emotions in the post-treatment period can be conceptualised as a ‘new normal’.